Складчато-надвиговый пояс Приполярного Урала: актуализированная геологическая модель и перспективы крупных открытий - Соборнов К.О.; Данилов В.Н.; Приймак П.И.; Никонов Н.И. (Общество с ограниченной ответственностью «ВНИГНИ-2», 2016)
Integrated interpretation of geological and geophysical data provided a new insight into structure and petroleum habitat of the Polar Urals foldbelt. The study shows that the deformations observed in the Polar Urals foreland are mainly related to the thrusting and detachment faulting. The principal detachment in the sedimentary cover is provided by the Upper Ordovician evaporates pinching out in the area of the Chernyshov swell. The updated structural model permits the identification of the new large exploration opportunities. Bulk of the new gas reserves is predicted in the folded zone in front of the Urals involving large thrust-related closures. Significant oil discoveries are expected in the transition zone between the Chernyshov swell and the Kosyu Rogov foredeep which is a focus of regional hydrocarbon migration. New seismic data provide evidence for the considerable development of the hypogenic karst and dolomitization of the Serpukhovian sulphates and carbonates capable of increasing the reservoirs porosity.
Keywords: URALS FORЕLAND; CHERNYSHOV SWELL; SEISMIC INTERPRETATION; FOLD-THRUST BELT; OIL; GAS; 553.98